2021
DOI: 10.1111/ecc.13440
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported signs and symptoms of secondary upper limb lymphoedema related to breast cancer treatment: Systematic review

Abstract: Introduction Breast cancer survivors with secondary upper limb lymphoedema (ULL) may report a wide range of self‐reported symptoms. At the moment, no overview of ULL‐specific symptoms is available. The first aim, therefore, was to compare the prevalence rates of self‐reported signs and symptoms in people with and without secondary ULL due to breast cancer treatment. The second aim was to determine whether symptoms of lymphoedema could be predictive for the development of ULL. The third aim was to describe the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 57 publications
(285 reference statements)
2
13
0
Order By: Relevance
“…Decreased sensitivity for mechanical stimuli has previously been reported in the surgical region compared to the same region on the non-affected side, both in breast cancer participants with and without pain in this area [41]. As described in literature, local sensory loss seems prevalent after breast cancer surgery [4,41], although not necessarily related to the presence of measurable BCRL. The twopoint discrimination threshold does not significantly differ between groups after correction for multiple testing.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Decreased sensitivity for mechanical stimuli has previously been reported in the surgical region compared to the same region on the non-affected side, both in breast cancer participants with and without pain in this area [41]. As described in literature, local sensory loss seems prevalent after breast cancer surgery [4,41], although not necessarily related to the presence of measurable BCRL. The twopoint discrimination threshold does not significantly differ between groups after correction for multiple testing.…”
Section: Discussionsupporting
confidence: 52%
“…A recent review revealed that a total of 35 signs and symptoms of BCRL have been described in the literature [4]. The main symptoms reported were swelling, heaviness, and tightness/firmness of the arm [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in addition to lymphedema, breast cancer patients might also suffer other conditions after surgery, radiotherapy, or chemotherapy, such as neuropathy up to 30%, myofascial pain up to 44%, fatigue up to 94%, 20-40% upper body problems, and 18-54% functional limitations [2][3][4][5][6][7][8], which contribute to patients' particular complaints, such as arm pain, numbness, or feeling of heaviness [9,10]. Women with lymphedema more frequently report pain and demonstrate bilateral impairments in shoulder range of motion, greater restrictions in upper limb activities and upper limb strength, and sensory disturbances compared to women without lymphedema [9,11]. While there are several studies in the literature on physical, functional, and emotional problems in women with BCRL, the effects of lymphedema on sensory parameters have not been explored.…”
Section: Introductionmentioning
confidence: 99%